Indonesian National Security During Pandemic - Ni Kadek Nita Noviani Pande; Ayu Gde Chrisna Udayanie (Catuspata, 2023)
The background of this article is based on national security issues during the Covid-19 pandemic. Coronavirus diseases-2019 or known as COVID-19 originated in the city of Wuhan, Hubei Province, China. The virus first appeared at the end of 2019. Its spread is very fast and has plagued almost all countries in the world, including Indonesia. COVID-19 has an impact on all sectors, the economy, the tourism industry, agriculture, education, health services, security and defense, and many more. The research method used in this study using qualitative research. Data was obtained through previous research in the form of books, journals, scientific articles, and news from official websites. The results of this study indicate that the concept of national security contained in the state constitution is urgent to be presented.